Accounting information system security: A survey of e-commerce companies in Malaysia / Raja Haslinda Raja Mohd Ali and Rafeah Mat Saat - Raja Mohd Ali, Raja Haslinda; Mat Saat, Rafeah (2004)
The reliance on information and rapidly changing technology in Malaysia has forced organizations especially in e-commerce industry to implement comprehensive information security programs and procedures to protect their information assets. Failure to secure information or to make it available when required to those who need it can, and does, lead to financial loss. Professionals and managements should realize the importance of having secured system. In recent years, the cases of computer fraud, hackers and computer crime is unavoidable unless stringent protections being implemented. Tremendous increase in computer related fraud in Malaysia business organizations would reduce the confidence of the shareholders towards companies. This paper intends to identify the significant security breaches that actually faced by the computerized accounting systems in ecommerce industry. It also investigates the controls to prevent and detect security breaches that have been implemented in this industry.